Predictors of Locoregional Outcome in HER2-Overexpressing Breast Cancer Treated With Neoadjuvant Chemotherapy. (August 2015) - Arsenault, Daniel; Hurley, Judith; Takita, Cristiane; Reis, Isildinha M.; Zhao, Wei; Rodgers, Steven; Wright, Jean L.
<x xml:space="preserve">Abstract</x> Objectives: We identified prognostic factors for locoregional recurrence (LRR) in a cohort of patients with HER2-overexpressing breast cancer treated with neoadjuvant chemotherapy (NACT). Methods: We reviewed records of 157 patients with HER-overexpressing tumors who received NACT between May 1999 and December 2009 and collected demographics, disease/treatment characteristics, and clinical outcome. We estimated rate of LRR by the method of cumulative incidence. Results: Presentation was 33% stage II and 67% stage III; 29.9% were clinically node positive. All patients received NACT, 94% trastuzumab containing. 90.4% had mastectomy and 6.4% breast-conserving surgery; 3.2% had no surgery. Among surgical patients, 48% were pathologically N0, 28.8% had 1 to 3 positive nodes, and 23.7% had ≥4 positive nodes. 79.6% received radiation therapy (RT) to the breast/chest wall±supraclavicular field. Median follow-up was 43 months. Three-year cumulative incidence of LRR was 8.2%; 50% of LRR had a regional component. Predictors for LRR included use of RT (HR=4.70, P=0.006), lymph node positivity (≥4 vs. 0 HR=19.99, P=0.008; 1 to 3 vs. 0 HR=10.8, P=0.031), and ER status (negative vs. positive HR=6.02, P=0.006). The only risk factor for regional failure specifically was residual nodal disease (≥4 HR=6.5, 1 to 3 HR=5.1, P=0.031). Conclusions: In a cohort with stage II to III HER2-overexpressing breast cancer treated predominantly with trastuzumab-containing NACT followed by mastectomy±RT, we identified omission of RT, negative ER status, and residual positive lymph nodes as significant predictors of LRR, with 50% of LRR having a regional component.